562 ACQUIRED CORONARY FISTULA IN A PATIENT WITH CONGENITAL AORTIC STENOSIS TREATED WITH PERCUTANEOUS VALVULOPLASTY. (15th December 2022) - Calvelli, Pierangelo; Bianco, Francesco; Mancuso, Cinzia; Pasceri, Eugenia; Canepa, Annalisa; Mascaro, Giuseppina; Indolfi, Ciro; Aquila, Iolanda
Abstract: Introduction: coronary fistulas are abnormal communications between coronary arteries and an adjacent structure (vessel or cardiac chamber). They can be congenital or acquired and have traumatic, spontaneous or iatrogenic origin. Aim: we report the case of a coronaro-cameral fistula in an asymptomatic 23-year-old male, with a congenital aortic stenosis treated with two percutaneous valvuloplasties in the first year of life, who was evaluated in our Division of Cardiology. Methods: transthoracic echocardiography and angio-CT with 3D reconstructions were performed. Results: echocardiography showed a dilated ventricle with ipertrabeculated aspect and a mildly reduced ejection fraction (47% Simpson), a moderate mitral regurgitation, a moderate/severe aortic insufficiency (PHT 242 ms) and a moderate aortic stenosis (valvular area 1.1 cm2; Gr max/mid 98/61 mmHg). In parasternal long axis view we appreciated a non-echogenic space between the aortic root and the right ventricle, communicating with left ventricular cavity. Angio-CT allowed us to appreciate a fistula connecting left ventricular outflow tract and right coronary artery, which was markedly dilated and tortuous. Surgical correction was deemed necessary for the patient, because of the severity of coronary dilatation and aortic and ventricular disfunction. Conclusions: acquired fistulas are rare findings which can complicate surgical and non-surgical interventions. They are more often right-sided, but left fistulas have also been described. Integrated imaging is particularly useful for correct definition of anatomy and for surgical planning.